Bilateral Kienböck disease; a literature review and case presentation - Ahmadreza Afshar; Mohammad Javad Shariyate; Ali Tabrizi (Trauma Case Reports)
In this case report and comprehensive literature review, we present the prevalence and clinical variability of bilateral Kienböck disease, focusing on its frequency, gender and age distribution, ulnar variance, and the synchronicity and stage congruence of symptoms bilaterally. A systematic review of the literature and a detailed case presentation revealed that bilateral Kienböck disease, accounting for 3 to 7.3% of cases, may be underdiagnosed due to its variable and often asynchronous presentations between the left and right wrists. Our findings highlight the need for thorough bilateral evaluations in patients with Kienböck disease to ensure a comprehensive diagnosis and to guide optimal management. This study advocates for heightened clinical vigilance and advances a nuanced understanding of this complex condition.